Respuestas
Respuesta dada por:
1
Hola ;)
aquí la solución
la respuesta es la A
ya q
(2a+7)(2a-7)
=4a^2-14a+14a-49
=4a^2-49
Espero que te haya servido
aquí la solución
la respuesta es la A
ya q
(2a+7)(2a-7)
=4a^2-14a+14a-49
=4a^2-49
Espero que te haya servido
Respuesta dada por:
0
Hola!
![(2a + 7)(2a - 7) \\ \\ 4 {a}^{2} - 14a + 14a - 49 \\ \\ 4 {a}^{2} - 49 (2a + 7)(2a - 7) \\ \\ 4 {a}^{2} - 14a + 14a - 49 \\ \\ 4 {a}^{2} - 49](https://tex.z-dn.net/?f=%282a+%2B+7%29%282a+-+7%29+%5C%5C++%5C%5C+4+%7Ba%7D%5E%7B2%7D++-+14a+%2B+14a+-+49+%5C%5C++%5C%5C+4+%7Ba%7D%5E%7B2%7D++-+49)
Alternativa a.
Alternativa a.
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años